Information and communication technology development and health gap nexus in Africa - Ebenezer Toyin Megbowon; Oladipo Olalekan David (Frontiers Media S.A., 2023)
IntroductionDevelopment of information and communication technology has been identified as a tool for fast and effective information gathering and dissemination, and as a means through which almost every social and economic sector (including the health sector) could achieve economic, operational, and service delivery efficiencies that can enable the realization of targeted outcomes. ICT can serve as a tool for achieving international agreements (including the Alma Ata Declaration of 1978), thereby accelerating the achievement of various global development targets.MethodsConsequently, based on a sample of 38 countries from 2000 to 2018, this study investigates the effect of ICT development on the health gap, and whether the effect varies by gender and sub-region in Africa. The dependent variable (health gap) was measured as the difference between the achieved life expectancy at birth of 60 years and the Alma Ata Declaration of 1978 targeted life expectancy at birth of 60 years. The main independent variables are ICT indicators (ICT index, mobile cellular subscriptions, and internet access), while the gross domestic product (GDP), which is the measure of economic growth, healthcare expenditure, urbanization, and labor market outcome, is employed as control variables. The effect was examined using Driscoll-Kraay standard errors, feasible generalized least squares (FGLS), and panel-corrected standard error (PCSE).Results and discussionThe findings of the Driscoll-Kraay standard errors estimation technique supported by those of FGLS and PCSE suggest that ICT does act as an indispensable stimulator for Africa to significantly exceed the international health target of life expectancy at birth of 60 years. It can be concluded that African leaders need to take advantage and maximize the health-enhancing potential of the internet component of ICT through relevant policies that would improve internet coverage, connectivity, and access for individuals and health institutions.